Social reintegration and rehabilitation of obstetric fistula patients before and after repair in Sub-Saharan Africa: A systematic review - Shallon, Atuhaire; Ojengbede, Oladosu A.; Mugisha, John Francis; Odukogbe, Akin-Tunde A. (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To review how social reintegration and rehabilitation processes are being executed among obstetric patients in Sub-Saharan Africa and highlight projects and programs involved. Methods: This is a systematic review involving a search of relevant literature from PubMed, Google scholar, PsychINFO, African Journals Online, Australian Journals Online, and open access journal of international organizations such as WHO, UNFPA, USAID, Engender Health, Fistula Foundation, and Fistula Care Plus published between 1978 to date. Of the 46 articles identified, 25 were suitable for achievement of this study’s purpose. Results: Sub-Saharan African countries have recognized the overall burden of obstetric fistula and have devised strategies for its’ holistic management. Most countries have National Obstetric Fistula Strategic Frameworks which emphasize multi-sectoral and multidisciplinary approaches other than medical paradigm. Extraordinary among others are: Nigeria, Uganda, Tanzania and Guinea while some countries such as Benin Republic, Chad, Malawi, Mali, and Zambia lack support the at policy level, and have inadequate community outreach programmes. Social reintegration and rehabilitation have been done through the identification of individual patient’s need/s. Upon discharge from hospital, they are counseled, given soap, clothes, transportation fund and are referred to community based projects for elementary education and skills development. Projects and programmes aiming to combat obstetric fistula and restore patients’ self-worth and dignity are: Lamaneh Suisse, and Delta Survie in Mali, Dimol in Niger, Medecins Sans Frontieres (MSF) in Burundi, FORWARD in Nigeria and Sierra Leone, Handicap International in Benin Republic, Women For Africa in Ghana and Liberia, TERREWODE and CoRSU both in Uganda, Hamlin Fistula Ethiopia in Ethiopia, and Safe Motherhood Initiative, Fistula Foundation, Fistula Care Plus, Engender Health, UNFPA, AMREF for Health, WHO and others which cut across the region. Conclusions: Most Sub-Saharan countries have registered progress in assuring effective social reintegration and rehabilitation of obstetric fistula patients although some are still grappling with the issue due to lack of political commitment and inadequate outreach programmes. There is scanty information regarding reintegration and rehabilitation before obstetric fistula repair and yet it would hasten physical and mental wellbeing of the patients as they await repair.